The ISApl12 Dimer Circular Intermediate Participates in mcr-1 Transposition - He, Yu-Zhang; Li, Xing-Ping; Miao, Yuan-Yuan; Lin, Jun; Sun, Ruan-Yang; Wang, Xiao-Pei; Guo, Ya-Ya; Liao, Xiao-Ping; Liu, Ya-Hong; Feng, Youjun; Sun, Jian (Frontiers in Microbiology, 2019)
Objectives: The mobile colistin resistance gene mcr-1 is a serious threat to global human and animal health. The composite transposon Tn6330 and its circular intermediate were proposed to be involved in the spread of mcr-1 but their roles remain poorly understood. Methods: To further explore the intermediates during the transposition of Tn6330, we engineered Escherichia coli strains that carry an intact Tn6330 transposon or its deletion derivatives. PCR assays were performed to detect IR-IR junctions and possible circular intermediates. We carried out transposition experiments to calculate transposition frequency. The transposition sites were characterized by whole genome sequence and ISMapper-based analyses. Results: The presence of an intact Tn6330 was demonstrated to be essential for the successful transposition of mcr-1, although both Tn6330 and Tn6330-ΔIR could form circular intermediates. The insertion sequence junction structure was observed in all constructed plasmids but the ISApl1 dimer was only formed in one construct containing an intact Tn6330. The average frequency of mcr-1 transposition in an E. coli strain possessing an intact Tn6330 was ∼10-6 per transformed cell. We identified 27 integration sites for the Tn6330 transposition event. All the transposition sites were flanked by 2 bp target duplications and preferentially occurred in AT-rich regions. Conclusion: These results indicate that mcr-1 transposition relies on the presence of an intact Tn6330. In addition, formation of the tandem repeat ISApl12 could represent a crucial intermediate. Taken together, the current investigations provide mechanistic insights in the transposition of mcr-1.